Análisis de los procedimientos de control de ingresos y egresos de la comercializadora CEVACA de la ciudad de Ventanas - Naranjo Villalva, Julissa Beatriz (2021)
This case study was carried out at the “Cevaca” Marketing Company; company dedicated to the commercialization and drying of rice, corn and soybeans. The problem is based on the lack of control procedures in the records of income and expenses. The objective of the research is to analyze the control procedures of commercial transactions in order to know what are the factors that intervene in the ineffective handling of accounting information. The applied methodology has the types of field and descriptive research. The inductive and deductive method was used. In addition, the techniques of interviewing the owner of the marketer and direct observation of the financial statements were used, where the following results were obtained: The purchase process presents drawbacks in the issuance of purchase settlements. Suppliers do not provide the corresponding information (RUC and RISE). Sales are executed without the delivery of enabling documents (invoices and vouchers) at the request of the clients; While in the profitability analysis it has a gross profit margin of -3% where the indicator recommended by the Superintendency of Companies and Insurance is 36.96%, the net profit margin has a loss with a result of -8% and the Calculation of the current ratio denotes that the company has liquidity to do with short-term obligations, but does not reach the results expected by the Supercías, since its result is 0.67 and the recommended indicator 0.84.